Short-termism in urban development: The commercial determinants of planetary health - Daniel Black; Geoff Bates; Rosalie Callway; Kathy Pain; Ed Kirton-Darling (Earth System Governance)
This article focuses on how short-termism impacts on the quality of urban development and, in turn, both population and planetary health. The first section of the paper clarifies key terms - short-termism, health, urban development and upstream - then summarises the context of urban development in the United Kingdom, and the evidence linking urban environments to population and planetary health. The main analysis section draws on data from interviews with 132 participants carried out between May and September 2021. Using the Commercial Determinants of Health framework, six thematic areas are identified: Policy & Political Economy; Legislation and Regulation; Commercial Actors; Underlying Drivers (Power); Externalities; and Partnership. Analysis suggests 16 key messages, the majority of which point to the need for stronger government intervention, a position supported by private sector, if fairly enacted.